Von der konventionellen Bildgebung zum Cutting Edge Imaging in der Rheumatologie - Simon, David; Kemenes, Stephan; Minopoulou, Ioanna; Kleyer, Arnd (Zeitschrift für Rheumatologie, 2023)
Imaging instruments, such as conventional X‑ray, ultrasound and magnetic resonance imaging (MRI) are now fully established and highly valued in the care of rheumatology patients. However, the information provided by these imaging modalities in their current form is of limited utility for the prognostic prediction of individual patient outcomes. This article illuminates an important part of the development of imaging and shows that the vision of personalized medicine is becoming increasingly more tangible due to the further development of high-resolution imaging techniques, molecular imaging and artificial intelligence.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Artificial intelligence; Magnetic resonance imaging; Molecular imaging; Personalized medicine; Sonography